1998
DOI: 10.1177/019262339802600101
|View full text |Cite
|
Sign up to set email alerts
|

Normal Ultrastructure of the Kidney and Lower Urinary Tract

Abstract: The mammalian urinary tract includes the kidneys, ureters, urinary bladder, and urethra. The renal parenchyma is composed of the glomeruli and a heterogeneous array of tubule segments that are spccialized in both function and structure and are arranged in a specific spatial distribution. The ultrastructure of the glomeruli and renal tubule epithelia have been well characterized and the relationship between the cellular structure and the function of the various components of the kidney have been the subject of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 275 publications
2
31
0
Order By: Relevance
“…Classical methods of light microscopy were used in studies by Leeson (1962) and Ersoy et al (2006) in rats and Jost et al (1989) in humans. The methods of electron microscopy were used by Walker (1960) in mice, Burke (1976) and Verlander (1998) in rats, Richter & Moize (1963) in different mammalians, Monis & Zambrano (1968) in humans and Hoyes et al (1972) in human fetuses. In our work we described some histological methods (light microscopy, transmission and scanning electron microscopy) used for investigation of ultrastructure of human's urinary epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Classical methods of light microscopy were used in studies by Leeson (1962) and Ersoy et al (2006) in rats and Jost et al (1989) in humans. The methods of electron microscopy were used by Walker (1960) in mice, Burke (1976) and Verlander (1998) in rats, Richter & Moize (1963) in different mammalians, Monis & Zambrano (1968) in humans and Hoyes et al (1972) in human fetuses. In our work we described some histological methods (light microscopy, transmission and scanning electron microscopy) used for investigation of ultrastructure of human's urinary epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…26 The filtration barrier in the glomerulus has three layers: the fenestrated endothelium, the glomerular basement membrane and the podocytes together with a slit diaphragm between the digitations of the podocyte foot processes. 30 The basement membrane is negatively charged because of the presence of anionic sites of glycosaminoglycans, principally heparan sulfate in the lamina rara. Morphometric studies in rats have shown that the size of Bowman's capsule and the capillary tuft generally not only increases with advancing age but also may vary between strains.…”
Section: Glomerulusmentioning
confidence: 99%
“…The morphology of renal tubular epithelium also varies considerably in different sections of the nephron. Proximal tubular cells have abundant long microvilli on the luminal side while other segments either have stubby microvilli or smooth surfaces [37]. These features also affect the flow velocity and crystal movement.…”
Section: Animal Modelsmentioning
confidence: 99%